Corporate ESG Performance, Digitalization, and Human Capital Investment Efficiency: An Empirical Evidence from Chinese Firms - Mustafa, Ghulam; Hussain, Altaf; Rehman, Muhammad Atiq ur; Hassan, Muhammad (Pakistan Journal of Humanities and Social Sciences, 2025)
This study explores the effect of environmental, social, and governance (ESG) performance and digitalization on human capital investment (HCI) efficiency in Chinese firms. Using data from 319 A-share market-listed Chinese firms for the period 2019-2023, the panel least square approach is used for the estimation. The empirical results show that ESG performance, alongside digitalization, company size, and stock prices, positively influences HCI efficiency in Chinese enterprises. Furthermore, the interaction between ESG performance and digitalization acts as a catalyst in the ESG-human capital relationship by enhancing labor training opportunities and skills driving technological advancements in corporate operations. The relationship between ESG performance and digitalization is multifaceted and dynamic; digitalization can improve ESG performance, while strong ESG performance supports digitalization. Together, these factors synergistically enhance HCI efficiency.